Difference in the Motivational Beliefs of Asian American and Non-Asian Students - Eaton, Martin J.; Dembo, Myron H. ([S.l.] : Distributed by ERIC Clearinghouse, 1996)
This investigation explored the differences in the motivational beliefs of ninth-grade Asian American and non-Asian students. Participants were 154 Asian Americans of various ethnicities and 372 non-Asians. Student beliefs about achievement were explored through a questionnaire developed for the study. The statistical findings suggest that the differences in type of beliefs between the two groups may help to explain their achievement behavior. More specifically, Asian American students' fear of the negative consequences of academic failure best explained their performance on the achievement task, while fear of failure least explained the non-Asian students' performance. Asian American students reported significantly lower levels of situational self-efficacy beliefs than did their non-Asian counterparts. However, Asian students outperformed non-Asian students on the achievement task. The cultural belief, fear of academic failure, better explained achievement motivation for Asian Americans than did self-efficacy beliefs. A major implication of this investigation is that more attention should be given to how motivational beliefs elicit different responses in different cultural/ethnic groups. (Contains 5 tables and 85 references.) (Author/SLD)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (New York, NY, April 8-12, 1996).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Asian American Students; Asian Americans; Behavior Patterns; Beliefs; Cultural Differences; Ethnic Groups; Grade 9.; High School Students; High Schools; Self Efficacy; Student Attitudes; Student Motivation; White Students; Reports, Research; Speeches/Meeting Papers